Mengembangkan Keterampilan Menulis Teks Daily Activity Yang Sesuai Dengan Struktur Kalimat Pada Peserta Didik Kelas VII Di SD-SMP Negeri Satu Atap 4 Gunungsari - Najamudin, Najamudin (Literasi: Jurnal Pendidikan Guru Indonesia, 2023)
The language of international communication is English, which is the connecting language between nations in the world in various fields of life. As a global language, a means of communication and an international information medium, English is studied and included in the mandatory curriculum for many countries in the world, including Indonesia. One of the English language skills is the activity of writing daily routines or daily activity text. Difficulty compiling daily routine texts by students because the content and ideas of their writing have not been developed properly; In fact, his writing only consists of a few sentences and is not continuous, and is not arranged according to chronology. The author thinks that a special method or approach is needed to improve the abilities and skills of 24 students in class VII of SD-SMP Negeri Satu Roof 4 Gunungsari to be able to master the competency of writing daily activity text properly and correctly. To explore interest and talent in writing daily routines in English, the classroom action method was used with a problem based learning (PBL) model approach. The results of the study concluded that there were 18 students who were declared complete and as many as 6 students who were declared incomplete, the minimum completeness criteria was 75. The students' highest score was 88 and the lowest score was 60. The score above the KKM was 61% or 11 students. Student learning outcomes improved after developing the learning model from conventional to PBL.